A new conceptual model for international franchising. (September 2018) - Rosado-Serrano, Alexander; Paul, Justin
Highlights: Develop a model on International Franchising partnerships integrating factors determining the franchise formation, expansion and performance. Discuss how these partnerships develop and how they differ. Derive theoretical propositions for future research in academia and for practice in the industry. Abstract: International franchising has been widely studied from the franchisor perspective, as it relates to why and how firms decide to expand by viewing it as a uni-directional perspective. With the increased volume of international franchising businesses, theory development that considers multidimensional elements such as distance, trust and its effects on franchise relationship and the system's performance is needed. The purpose of this paper is to develop a conceptual model on international franchising partnerships that integrates factors determining franchise formation, expansion and performance grounded in Relational Contracting Theory. The uniqueness of the proposed model is on its originality as a dynamic behavioral theoretical model to address the possibilities for value creation, performance improvement and minimizing failure probability in franchise systems which is important for managers as well as researchers.